Transformasi Pelayanan Administrasi: Studi Kasus Pionirs Di Kota Pontianak - Utami Nur; Adila Puspa Hestiantini; Dita Purnama (Universitas Mbojo Bima, 2025)
Digitalization of public services at the Pontianak City Population and Civil Registration Service is implemented through an online service website which is usually called PIONIRS (Pelayanan Online dari Rumah Sendiri / Online Services from Home). The aim of this research is to find out how PIONIRS is implemented as a form of digitalization of public services in Pontianak City based on the three principles of agile governance from Luna, Kruchten, and Moura (2015), namely Based on quick wins, Systematic and adaptive approach, and Simple design and continuous refinement. This research uses qualitative research with a case study approach. Data collection techniques in this research are through primary sources, namely interviews, surveys, and observations. The informants in this research were determined purposively. The informants were considered competent in relation to PIONIRS in Pontianak City. All fields because it concerns all services at the Pontianak City Population and Civil Registration Service. The fields that handle PIONIRS applications/websites are Management of Population Administration Information (PIAK) and Data Utilization at the Pontianak City Population and Civil Registration Service. In this research, the Miles & Huberman interactive model was used to analyze the data qualitatively. PIONIRS has been a transformative solution for Pontianak City, streamlining administrative processes and providing residents with a user-friendly, accessible platform for population services. The implementation of agile governance principles has enabled quick wins, systematic and adaptive approaches, and continuous refinement, resulting in a successful and efficient online service for the community.